Time to Reevaluate the Away Rotation: Improving Return on Investment for Students and Schools. (April 2019) - Griffith, Max; DeMasi, Stephanie C.; McGrath, Abigail J.; Love, Jeffrey N.; Moll, Joel; Santen, Sally A.
Abstract : Away rotations are common among senior medical students preparing to apply for residency. For competitive specialties, multiple away rotations may be viewed as a de facto requirement for a strong application. Although away rotations are often valuable learning experiences, a variety of noneducational factors motivate students to enroll, including the need for letters of recommendation, students' uncertainty regarding their strength as applicants, perceived competitiveness of residency applications, and conflicting guidance from advisors. Students who enroll in away rotations often benefit from a novel educational environment, opportunities for career exploration, and the chance to assess "fit" with a program. Yet away rotations also come at a significant cost. Students must deal with the time and expenses of rotating at multiple institutions. The application process for away rotations is expensive, disjointed, and inefficient. Students must work hard to make an impression on host institution faculty, and risk hurting their residency applications with a negative letter of recommendation. To reduce the burden of away rotations, future research should assess the impact of multiple away rotations on success in the Match. Allowing students limited access to letters of recommendation content would allow students and advisors to make informed decisions regarding additional rotations. Students would benefit from greater standardization of the application process for away rotations, with uniform dates, timely acceptances and rejections, and a cap for the number of applications per student. Students can maximize their returns by targeting away rotations that provide the most diverse educational experiences and valuable letters of recommendation.